Pengaruh Pembiayaan Sindikasi Terhadap Peningkatan Portofolio Pembiayaan Pt Bank Sumut Unit Usaha Syariah - Syahla, Nurul; Tambunan, Khairina (Regress: Journal of Economics & Management, 2022)
This study aims to determine the effect of syndicated financing on increasing the financing portfolio of PT. Bank Sumut Unit Usaha Syariah. Syndicated financing emerged to respond to the growing corporate business and capture infrastructure financing because the need for corporate and infrastructure financing funds was very large. One of the benefits of syndicated financing is the increase in ujrah/fees that can affect the financing portfolio. The method used is a quantitative method. The primary data in this research is in the form of documentation based on the financial statements & reports of an independent accountant (Final Report) of PT. Bank Sumut in 2018 to 2021, and literature study in obtaining theories and those related to this research. Based on the results of the study, it was concluded that syndicated financing could increase the financing portfolio of PT. Bank Sumut Unit Usaha Syariah.